Die Spook van Uniondale - Smith, Pierre (Film director); Storm, Willemien; Tas, Adam; Van Graan, Tanya; Zimmermann, Ivan; Moving Billboard Picture Company; Leomark Studios (Firm) ([Randburg, South Africa] : Moving Billboard Picture Company, 2014)
Stefan is driving through the countryside to visit his parents for Easter weekend when he sees a strange-looking woman standing at the side of the road. Just then, his car breaks down. Stefan pushes the car into the nearby town of Uniondale, and leaves it with the only mechanic not closed for the holiday.
Originally produced as a motion picture in 2014
Adam Tas, Tanya Van Graan, Ivan Zimmermann, Andre Stolz, Tobie Cronje, Andre Schwartz, Christina Knight, Nelda Jansen Van Rensburg, Jakkie Louw.
Cinematographer, Trevor Brown ; editor, Bruce McLaren-Lyall ; music, Vaughn Van Zyl.
In Afrikaan with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 25, 2018)
Keywords: Haunted places -- South Africa -- Uniondale -- Drama; Ghost films; Romance films; Feature films; Internet videos; Streaming video